Ionospheric disturbances during magnetic storms at SANAE - Hiyadutuje, Alicreance (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2017)
The coronal mass ejections (CMEs) and solar flares associated with extreme solar activity may strike the Earth's magnetosphere and give rise to geomagnetic storms. During geomagnetic storms, the polar plasma dynamics may influence the middle and low-latitude ionosphere via travelling ionospheric disturbances (TIDs). These are wave-like electron density disturbances caused by atmospheric gravity waves propagating in the ionosphere. TIDs focus and defocus SuperDARN signals producing a characteristic pattern of ground backscattered power (Samson et al., 1989). Geomagnetic storms may cause a decrease of total electron content (TEC), i.e. a negative storm effect, or/and an increase of TEC, i.e. a positive storm effect. The aim of this project was to investigate the ionospheric response to strong storms (Dst < -100 nT) between 2011 and 2015, using TEC and scintillation measurements derived from GPS receivers as well as SuperDARN power, Doppler velocity and convection maps. In this study the ionosphere's response to geomagnetic storms is determined by the magnitude and time of occurrence of the geomagnetic storm. The ionospheric TEC results of this study show that most of the storm effects observed were a combination of both negative and positive per storm per station (77.8%), and only 8.9% and 13.3% of effects on TEC were negative and positive respectively. The highest number of storm effects occurred in autumn (36.4%), while 31.6%, 28.4% and 3.6% occurred in winter, spring and summer respectively. During the storms studied, 71.4% had phase scintillation in the range of 0.7 - 1 radians, and only 14.3% of the storms had amplitude scintillations near 0.4. The storms studied at SANAE station generated TIDs with periods of less than an hour and amplitudes in the range 0.2 - 5 TECU. These TIDs were found to originate from the high-velocity plasma flows, some of which are visible in SuperDARN convection maps. Early studies concluded that likely sources of these disturbances correspond to ionospheric current surges (Bristow et al., 1994) in the dayside auroral zone (Huang et al., 1998).
Keywords: Uncatalogued